Theoretical investigation of the valence states in Au via the Au–F compounds under high pressure. Issue 32 (26th July 2019) - Liu, Guangtao; Feng, Xiaolei; Wang, Linyan; Redfern, Simon A. T.; Yong, Xue; Gao, Guoying; Liu, Hanyu
Abstract : A stable 6-fold coordinated AuF4 compound with anomalous Au 4+ is calculated to be stable under compression. Abstract : In addition to the known Au 3+ and Au 5+, it has recently been shown that Au is likely to possess unusual valence states in compressed Au–F compounds. However, our simulations reveal that polymeric ground-state AuF4 shows an unexpected 6-fold coordination rather than a 4-fold one, indicating that more complete comprehending on the anomalous Au 4+ is highly required. To fully understand the nature and origin of anomalous valence states in Au, we have extensively investigated the ground-state structures of Au–F compounds at high pressures using quantum mechanical computational methods. As a consequence, we identify several previously unreported (stable) AuF2, AuF3 and AuF4 structures. Our results extend the known polymorphism of AuF n compounds and offer a fundamental understanding of the origin of unusual valence states in Au that prevail at high pressure.